Attempts to quit smoking among Indonesian male smokers: findings from the 2011 and 2021 global adult tobacco survey (GATS) - Nohan Arum Romadlona; Siti Fatimah; Meirina Nur Asih Susanti; Muhammad Shaddam Naufal Alim (Berita Kedokteran Masyarakat, 2026)
Purpose: This study examines attempts to quit smoking patterns among Indonesian males using 2011 and 2021 GATS data to identify influencing factors. Methods: The study conducted a secondary analysis on male respondents aged 15 years and older with a history of smoking, consisting of current smokers and former smokers, utilizing a weighted sample. The outcome variable was attempts to quit smoking among male ever smokers. Independent variables involved sociodemographic characteristics, awareness of health consequences, and exposure to information about the dangers of smoking through various media. Results: The prevalence of attempts to quit smoking among Indonesian males increased from 29.8% in 2011 to 43.6% in 2021. In 2011, quit attempts were significantly associated with urban residence (aOR 1.46; 95% CI: 1.02–2.10), health awareness (aOR 2.26; 95% CI: 1.63–3.13), exposure to anti-smoking information from radio (aOR 1.45; 95% CI: 1.13–1.86), and television (aOR 1.47; 95% CI: 1.04–2.09). In 2021, significant factors included urban residence (aOR 1.27; 95% CI: 1.02–1.59), health awareness (aOR 1.76; 95% CI: 1.40–2.20), unemployment (aOR 1.61; 95% CI: 1.25–2.07), exposure to anti-smoking information from billboards (aOR 1.35; 95% CI: 1.09–1.68), and the internet (aOR 1.62; 95% CI: 1.31–1.99). These findings highlight the role of place of residence, awareness of health, and exposure to information about the dangers of smoking through various media in attempts to quit smoking. Conclusion: Public health initiatives should enhance awareness campaigns, target rural and lower-educated populations, strengthen tobacco control policies, adopt media strategies, and increase encouragement of health awareness to quit smoking across different demographic groups.